Internal Control System of the Enterprise as Instrument for Ensuring Economic Security - A. V. Guryanov; V. A. Plotnikov; A. M. Yusufova (Управленческое консультирование)
The Russian economy today faces serious problems due to external sanctions, which are aimed at weakening it in every possible way. This leads to the emergence of new and aggravation of existing problems in the field of ensuring the economic security of enterprises. Activities to manage the processes of protecting the economic interests of enterprises in these conditions need to be intensified. The functioning of the enterprise’s internal control system plays a significant role in this. Purpose of the study: to analyze the functioning of the enterprise’s internal control system in the context of solving the problems of ensuring its economic security. Research methods: analysis of the dynamics of risks and threats to the economic security of enterprises, functional analysis, methods of structural and comparative analysis, the study is based on the ideas of integrating enterprise management, which implies the integration of its various subsystems, in particular, internal control systems and ensuring economic security. The article substantiates the need to introduce and develop internal control at an enterprise and examines the importance of the internal control system as a factor in increasing the economic security of an enterprise. The main objectives of the economic security of an enterprise in this context are identified as: timely identification and prevention of adverse events in the activities of the enterprise; ensuring compliance with current legislation; asset protection; control of the reliability of the reporting provided; carrying out analysis of the processes of economic activity of the enterprise. These tasks correlate with the tasks of the enterprise’s internal control system.